2021
DOI: 10.1186/s12888-021-03596-2
|View full text |Cite|
|
Sign up to set email alerts
|

Functional neurologic disorders in an adult with propionic acidemia: a case report

Abstract: Background Inborn errors of metabolism are often characterized by various psychiatric syndromes. Previous studies tend to classify psychiatric manifestations into clinical entities. Among inborn errors of metabolism, propionic acidemia (PA) is a rare inherited organic aciduria that leads to neurologic disabilities. Several studies in children with PA demonstrated that psychiatric disorders are associated to neurological symptoms. To our knowledge, no psychopathological description in adult with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Chronic neurological and cognitive complications are frequent in PA, including movement disorders, spastic paresis, intellectual disability and strokes of basal ganglia [ 23 ]. Late manifestations of neuropsychological disorders, such as autism and borderline personality traits, have also been reported [ 24 , 25 ]. Other complications may include recurrent pancreatitis, adaptive immune defects, rhabdomyolysis, optic atrophy, hearing loss, premature ovarian failure, and chronic kidney disease [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic neurological and cognitive complications are frequent in PA, including movement disorders, spastic paresis, intellectual disability and strokes of basal ganglia [ 23 ]. Late manifestations of neuropsychological disorders, such as autism and borderline personality traits, have also been reported [ 24 , 25 ]. Other complications may include recurrent pancreatitis, adaptive immune defects, rhabdomyolysis, optic atrophy, hearing loss, premature ovarian failure, and chronic kidney disease [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was missing. The funding note is given below.…”
mentioning
confidence: 99%